A hospital-based estimate of major causes of death among under-five children from a health facility in Lagos, Southwest Nigeria: possible indicators of health inequality - Afolabi Bamgboye M; Clement Cecilia O; Ekundayo Adejuwonlo; Dolapo Duro (BMC, 2012)
Abstract Introduction Current evidence on the root-causes of deaths among children younger than 5years is critical to direct international efforts to improve child survival, focus on health promotion and achieve Millennium Development Goal 4. We report a hospital-based estimate for 2005-2007 of the major causes of death in children in this age-group in south-west Nigeria. Methods We used retrospective data from the intensive care unit of a second-tier health facility to extract the presenting complaints, clinical diagnosis, treatment courses, prognosis and outcome among children aged 6-59months. SPSS-19 was used for data analysis. Results Of the 301 children (58% males, 42% females) admitted into the ICU within the period of study, 173 (26%) presented with complaints related to the gastrointestinal system, 138 (21%) with respiratory symptoms and 196 (29%) with complaints of fever. Overall, 708 investigations were requested for among which were full blood count (215, 30%) and blood slides for malaria parasite (166, 23%). Infection ranked highest (181, 31%) in clinicians' diagnosis, followed by haematological health problems (109, 19%) and respiratory illnesses (101, 17%). There were negative correlations between outcome of the illness and patient's weight (r=-0.195, p=0.001) and a strong positive correlation between prognosis and outcome of admission (r=0.196, p=0.001). Of the 59 (20%) children that died, presentation of respiratory tract illnesses were significantly higher in females (75%) than in males (39%) (χ²=7.06; p=0.008) and diagnoses related to gastrointestinal pathology were significantly higher in males (18%) than in females (0%) (χ²=4.07; p=0.05). Majority of the deaths (21%) occurred among children aged 1.0 to 1.9years old and among weight group of 5.1-15.0kg. Conclusion The major causes of deaths among under-five years old originate from respiratory, gastrointestinal and infectious diseases - diseases that were recognized as major causes of childhood mortality about half a century earlier. Realization of MDG4 - to reduce child mortality by two-thirds - is only possible if the government and donor agencies look beyond the health sector to find hidden causative factors such as education and housing and within the health sector such as vibrant maternal, new-born, and child health interventions.